Advances in taxation. Vol. 22 - Hasseldine, John (Advances in taxation, 2015)
Advances in taxation publishes relevant, high-quality manuscripts from around the world addressing problems arising from federal, state, local and international taxation. The series uses a wide variety of research methods, including archival, experimental, survey, qualitative and legal approaches to address the problems and issues associated with taxation. Volume 22 of Advances in taxation continues this approach to taxation, looking at issues concerning challenges in tax administration, taxpayer decisions, ethical issues in taxation, and college savings plans.